Measurement properties of the Danish version of the Boston Carpal Tunnel Questionnaire - Mosegaard, Sebastian Breddam (JPRAS Open, 2021)
BACKGROUND AND AIMS: Patient reported outcome measures are often used in medical research to evaluate symptoms and functional status in patients. The Boston Carpal Tunnel Questionnaire is specifically designed to evaluate functional status and symptom severity in patients with Carpal Tunnel Syndrome. The aim of this study was to validate and examine the measurement properties of the Functional Status Scale and Symptom Severity Scale from the Danish translated Boston Carpal Tunnel Questionnaire. MATERIAL AND METHODS: We analyzed 88 prospectively enrolled patients in the validity and responsiveness group and 31 prospectively enrolled patients in the reliability group. Patients in the validity and responsiveness group answered the Quick Disabilities of the Arm, Shoulder and Hand Questionnaire and the Danish translated Boston Carpal Tunnel Questionnaire preoperatively and after surgery. Patients in the responsiveness group answered the same questionnaire two times prior to surgery. RESULTS: Responsiveness of the two subscales were high (Effect Size 0.99/1.76; Standardized Response Mean 0.86/1.50). Correlation to the Danish validated QuickDASH was high (rho 0.75/0.89). Test-retest reliability was high (ICC 0.94/0.90) and the internal consistency was high (Cronbach's alpha 0.93/0.92). CONCLUSION: Our study shows satisfactory results of both subscales of the Danish translated Boston Carpal Tunnel Questionnaire. This makes it highly useful when conducting research on patients with Carpal Tunnel Syndrome. TRIAL REGISTRATION: The Danish Data Protection Agency: jr. nr. 2007-58-0010